Internal and external labor markets an analysis of matched longitudinal employer-employee data - Abowd, John M. 1951-; Kramarz, Francis (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1997)
We decompose the real annual full time compensation costs of 1.1 million French workers followed over 12 years into a part that reflects their external opportunity wage and a part that reflects their internal wage rate. Using these components of compensation we investigate the extent to which firm-size wage differentials and inter-industry wage differentials are due to variability in the external wage (person effects) versus variability in the internal wage (firm effects). For France, we find that most of the firm-size wage effect and most of the inter-industry wage effect is due to person effects differences in the external wage rates.